Forensic imaging for causal investigation of death - Simons, David; Sassenberg, Alina; Schlemmer, Heinz-Peter; Yen, Kathrin (Korean journal of radiology, 2014)
Simons D, et al. Korean J Radiol. 2014 Mar-Apr;15(2):205-209. https://doi.org/10.3348/kjr.2014.15.2.205
Gesehen am 15.09.2020